DEVELOPMENT OF MODERATE ISLAMIC LAW - Kadarusman Kadarusman; anwar sholeh (Jurnal Ilmiah Pesantren, 2022)
This research departs from academic anxiety that Islam has not been able to answer the main problems of Muslims, namely first, the intellectual movement to make the Qur’an as a guide for social ethics, second, affirm and integrate knowledge, intellectuality and spirituality of Muslims,third, provide improvement of the spread of intolerance, extremism, radicalism and terrorism,fourth, placing Islamic teachings and culture in the context of the life of the nation and state. The formulation of the problem in this paper is how to develop a moderate legal paradigm in Islamic boarding schools, especially in PPMI Assalaam, and how the influence of the development of Islamic law on the development of PPMI Assalaam as an educational institution in Indonesia. This research is a qualitative research with content analysis method. The results showed that the development of moderate Islamic law at PPMI Assalaam was based on five main values, namely sourced from the Qur’an and as-Sunnah, wasatiyah life attitude, tasamuh life attitude, love of the study of the yellow book, and fiqh muqaranah insight. Methodically, can use saddudz dzari’ah by prioritizing benefit and avoiding mafsadat. This moderate Islamic law approach is oriented towards the ideals of realizing akhlaqul karimah and rahmatan lil’alamin (spreading love for the entire universe).